Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Apoidea (Spheciformes), Sphecidae (sensu stricto) - Gadallah, Neveen S. (Zootaxa, 2020)
An updated checklist of the Arabian species of Sphecidae is provided here. The list includes 70 identified valid species in 10 genera and four subfamilies: Ammophilinae (4 genera, 35 species), Chloriontinae (1 genus, 6 species), Sceliphrinae (2 genera, 8 species) and Sphecinae (3 genera, 21 species). Distributions, both on the Peninsula and extra-limital, are provided for each species and subspecies; four species (6%) are endemic to the Arabian Peninsula.